Carbon dioxide as a polymer feedstock. (1st September 2014) - Kemp, Terence
This review describes the progress made over the last 45 years since the seminal paper by Inoue's group in Tokyo on the utilisation of CO2 as a component of a polymerising system. This approach, rapidly taken up by others, focused initially on the copolymerisation of CO2 with an epoxide to yield a polycarbonate of high molecular weight. The initial catalysts for this process were based on organozinc compounds; these were extended to zinc phenoxides and then a series of metal-centred compounds, particularly metal porphyrins where the central metal was aluminium, cobalt, chromium, copper, manganese and various lanthanides. Later work developed in the direction of producing stereoregular polymers. The most recent advance has concerned the copolymerisation of CO2 with butadiene via a lactone intermediate; the butadiene and CO2 are initially combined with a Pd-centred catalyst to give the lactone which is then subjected to radical polymerisation. The significance of this work is that it offers a way of utilising what is normally a waste and environmentally hazardous product of many processes to synthesise a useful product.